Biomonitoring of metals for air pollution assessment using a hemiepiphyte herb (Struthanthus flexicaulis). (November 2015) - de Paula, Pedro Henrique M.; Mateus, Vinícius L.; Araripe, Denise R.; Duyck, Christiane B.; Saint'Pierre, Tatiana D.; Gioda, Adriana
Highlights: " erva de passarinho " used for the first time as biomonitor of air pollution. Comparison between the chemical composition of herb and PM2.5 . Enrichment factor and PCA–MRL used as source apportionment tools. Abstract: This work presents first results on elemental characterization of a parasite plant, Struthanthus flexicaulis, collected in urban, industrial and rural areas of Rio de Janeiro state, Brazil, in order to evaluate this plant as a biomonitor of metals pollution. The results were also compared to those obtained for fine particulate matter (PM2.5 ) collected from filters in nearby locales. The concentrations of PM2.5 measured in the filters were between 8.0 and 18.0 μg m −3 ; in some places, these measurements were higher than the 10 μg m −3, concentration recommended by the World Health Organization (WHO). Samples of the leaves and filters with PM were submitted to acid extraction, and the extracts were employed to determine major elements (Ba, Ca, Fe, K, Mg, P and S) by ICP OES and minor elements (Cr, Cu, La, Mn, Pb, Sr, Ti and Zn) by ICP-MS. Elements' extraction efficiency was evaluated by applying the method to the certified reference materials (CMR) of tomato leaves (NIST 1573 rd ) and urban dust (NIST 1648a). The concentrations of Ca, K and Mg were higher in leaves, while Ba, Ca, K and Zn showed higher concentrations in the PM. As expected, rural sites presented lower metal content. Enrichment factor (EF) and principal component analysis with multiple linear regression analysis (PCA–MLRA) were applied to the concentrations of elements in PM2.5 and in the leaves. Anthropogenic sources could be identified with both tools, which supports the use of S. flexicaulis as a biomonitor.